Development of chemistry module integrated with islamic values in thermochemistry and reaction rate for senior high school student - Anis Syafitri; Ayi Darmana (Pascasarjana Universitas Negeri Medan, 2018)
The chemistry module which integrated with Islamic values has already developed in thermochemistry and reaction rate. This research presented the availability of Islamic values in student’s handbook. The proper of chemistry module design based on BSNP criteria, and the response to chemistry module which integrated with Islamic values to teacher and university student. This research used the method of research and development. It consists of 3 steps which were analysis, design, and development. The instruments are checklist, questionnair based on BSNP criteria, and response questionnair. The result shown the lack of Islamic value in student’s handbook, chemistry module design is proper to used. The teacher and university student’s response are good and need no revision.Keywords:Islamic values; module development; statistics education research; students’ handbook